Experimental Research in English Language Teaching: A Peek from Undergraduate Students' Theses - Muhammad Affan Ramadhana; Deis Kondo Allo (Jurnal Studi Guru dan Pembelajaran, 2021)
This study focused on the undergraduate students’ theses submitted to the English Language Education study program in Universitas Cokroaminoto Palopo. A total of 53 theses between 2014-2018 were collected. The main purpose of this study is to capture the trends of experimental method used in students’ undergraduate research. The selected sample is only the theses submitted by students who have been finished study in not later than four years. Skill and elements, the technique of sampling, types of treatments, level of the school, types of the experimental method, and research instruments were analyzed. The results revealed that vocabulary is the most researched language skills. In terms of research designs, random sampling, pre-experimental, and test instruments dominated. Quasi-experimental only a little bit used that was found in 2014 of three theses used and true-experimental was not found at all. As for types of treatment (independent variables), learning media is dominantly used.